2023
DOI: 10.1007/s11356-023-30307-z
|View full text |Cite
|
Sign up to set email alerts
|

Does the setting of local government economic growth targets promote or hinder urban carbon emission performance? Evidence from China

Mo Chen,
Jijian Zhang,
Zhe Xu
et al.

Abstract: The management of growth targets drives China's rapid economic expansion and leads to potential carbon emission externalities. This paper empirically investigates the impact of economic growth target setting on carbon emission performance using panel data from 257 Chinese localities between 2004 and 2020. The analysis is conducted using 2SLS instrumental variable regression, cluster standard error regression, and the spatial Durbin model. The empirical findings indicate that local economic growth targets condi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…This, in turn, raises the financing constraints and operating costs for these companies. In response to these challenges and the need for survival, heavily polluting companies accelerate their efforts in technological advancement and green innovation, thereby improving their market competitiveness and mitigating the short-term negative effects of environmental target constraints on their performance [23]. However, it is important to note that the primary purpose of environmental target constraints and related regulations is to expedite the application of energy-saving and emission reduction technologies in heavily polluting companies, ultimately achieving green governance at the source.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This, in turn, raises the financing constraints and operating costs for these companies. In response to these challenges and the need for survival, heavily polluting companies accelerate their efforts in technological advancement and green innovation, thereby improving their market competitiveness and mitigating the short-term negative effects of environmental target constraints on their performance [23]. However, it is important to note that the primary purpose of environmental target constraints and related regulations is to expedite the application of energy-saving and emission reduction technologies in heavily polluting companies, ultimately achieving green governance at the source.…”
Section: Discussionmentioning
confidence: 99%
“…[20] based on the "Porter Hypothesis", examined the connection between government environmental regulations and the innovation capabilities of listed companies and found that in regions with well-designed environmental policies, the innovation capabilities of companies in competitive industries were significantly improved. Under the environmental pressure of meeting environmental objectives, enterprises are stimulated to actively innovate, increasing investment in the development of clean tech-nologies and services [21], thereby achieving a competitive advantage and high-quality development [22,23]. Innovation activities triggered by government environmental regulations typically have a lagged positive impact on economic benefits.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain empirical data that meet the requirements of the empirical research in this paper, the raw data obtained through the aforementioned methods were processed as follows: Firstly, city samples that underwent administrative division adjustments during the period of 2007-2017 and had significant missing data on key variables were excluded (such as Hami City, Danzhou City, Linzhi City, Nachu City, Shannan City, etc.) [53]. Secondly, specialized colleges and universities were excluded from the sample, as well as undergraduate colleges and universities with significant missing data on key variables (such as Kashi University, Changsha Medical College, Haikou College of Economics, Yunnan Police College, Southwest University of Political Science and Law, and other colleges and universities).…”
Section: Data Descriptionmentioning
confidence: 99%